Electronic Payment Technology and Tax Compliance : Evidence from Uruguay’s Financial Inclusion Reform - Brockmeyer, Anne; Saenz Somarriba, Magaly Vanessa (Washington, DC: World Bank, 2022)
Does the digitization of transactions in an economy increase tax compliance This paper studies the effect of financial incentives on the adoption of electronic payment technology and on tax compliance by firms. Exploiting administrative data and policy variation from Uruguay, the paper shows that i) consumer value-added tax rebates for credit and debit card transactions trigger an immediate 50 percent increase in the number of card transactions, ii) firms' use of card machines increases only on the intensive margin, and iii) tax compliance is unaffected. Endogenous card machine adoption and a low share of card sales in total reported sales can rationalize the findings.